Perceived quality in a triathlon - Angosto Sánchez, S.; Morán-Navarro, R.; Martínez-Cava, A.; López-Gullón, J.M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The interest in knowing participant perceptions regarding the quality and value of the service, has moved to sports events popular character. Knowing what are the determining factors for achieving the overall participant satisfaction, the organizers will favor greater loyalty and improved planning of upcoming events. Through a questionnaire, this study analyzes the different dimensions of quality, which has a triathlon, the perceived value and future intentions as perceived by the participant broker in the "XXVI National Triathlon Villa de Fuente Álamo". The results show that the logistics infrastructure dimension as the most valued factor in quality and communication the worse punctuation. The participants with greater experience obtained lower scores than the other groups.